Genetic polymorphism of prophenoloxidase A1 in Drosophila melanogaster. - Asada, N.; Fujimoto, K.; Tanaka, M.; Ohnishi, E. (Japanese Journal of Genetics [Idengaku Zasshi], 1993)
Electrophoretic variations of prophenoloxidase were obtained from natural populations of Drosophila melanogaster. A1, one of the 2 isoforms of the prophenoloxidases, is polymorphic: 10 fast-migrating and 2 slow-migrating types were found in polyacrylamide gel electrophoresis among 271 wild strains. The majority were the intermediate-migrating type. By use of these variants, A1 gene was mapped at 79.6 on the right arm of the second chromosome. By deletion mapping, its cytological position was located at 55A-B. In the electropherograms, hybrids between the types differing in mobility exhibited 3 bands, indicating that A1 is a dimeric protein. The gene for A1 is expressed through larval, pupal and adult stages.